2015
DOI: 10.1007/s13402-015-0251-7
|View full text |Cite
|
Sign up to set email alerts
|

IL6-induced metastasis modulators p-STAT3, MMP-2 and MMP-9 are targets of 3,3′-diindolylmethane in ovarian cancer cells

Abstract: From our data we conclude that DIM exhibits an anti-IL6-like activity by inhibiting p-STAT3 enhanced ovarian cancer cell proliferation and in vitro metastasis-associated events, i.e., adhesion, migration and invasion. Most significantly, MMP-2 and MMP-9, which are known to promote and enhance metastasis, were found to act as targets of DIM. This anti-IL6-like property of DIM may pave the way for the development of novel ovarian cancer preventive and/or therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…Activation of the IL-6/STAT-3 signalling axis is an important event in cancer which promotes tumorigenesis by regulating multiple survival signalling pathways in cancer cells [24]. IL-6 regulates nearly all hallmarks of cancer, such as inhibition of apoptosis [81,82], promotion of survival [8,75], proliferation [35,83], angiogenesis [10], invasiveness and metastasis [62,84], and is also known to regulate cancer cell metabolism (Fig. 2) [85,86].…”
Section: Role Of Il-6 and Associated Signalling In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of the IL-6/STAT-3 signalling axis is an important event in cancer which promotes tumorigenesis by regulating multiple survival signalling pathways in cancer cells [24]. IL-6 regulates nearly all hallmarks of cancer, such as inhibition of apoptosis [81,82], promotion of survival [8,75], proliferation [35,83], angiogenesis [10], invasiveness and metastasis [62,84], and is also known to regulate cancer cell metabolism (Fig. 2) [85,86].…”
Section: Role Of Il-6 and Associated Signalling In Cancermentioning
confidence: 99%
“…The formation and maintenance of this neovasculature remains always activated as an 'angiogenic switch' and helps tumour development [144]. STAT-3 activation by IL-6 facilitates angiogenesis in many cancers by inducing the expressions of VEGF, bFGF and MMP9 in tumour-associated endothelial cells, TAMs and MDSCs [60,84,143,145]. In addition, the Notch ligand, JAG-2, has been reported to be overexpressed in malignant plasma cells from MM patients, which induces the secretion of IL-6 and VEGF [146], whilst in breast cancer, Notch-3-dependent ERK activation via IL-6 appears to activate JAG-1 (Notch ligand) and CA-IX (a hypoxia survival gene).…”
Section: Invasion Metastasis and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Here we further showed that PIPKIγ-deficient SKOV-3 cells indeed exhibited lower mRNA levels of both MMP-2 and MMP-9. Although it has been suggested that the expression of MMP-2 and MMP-9 in ovarian epithelial cells can be regulated by STAT3 (49,50) and PIPKIγ depletion inhibits STAT3 activity similarly in OVCAR-8 cells as in SKOV-3 cells, no significant MMP-2 or MMP-9 reduction was detected in OVCAR-8 cells after PIPKIγ depletion. This suggests some complexity in the regulation of MMP-2 and MMP-9 in different types of epithelial ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 95%
“…In the past 5 years, niclosamide has been identified as a potential anticancer agent targeting multiple signaling pathways (eg, NF-κB, ROS, Notch, Wnt/b-catenin, and mTORc1) 1821. Recently, several studies have reported that niclosamide exhibits antiproliferative activity in head and neck, ovarian, breast, and hematologic cancer 2225. Till date, no studies demonstrating the therapeutic efficacy of niclosamide in colon cancer are available.…”
Section: Introductionmentioning
confidence: 99%